A sustainable process for biodiesel production using Zn/Mg oxidic species as active, selective and reusable heterogeneous catalysts - Navas, Marisa Belén (2020)
This paper describes the preparation and characterization of MgO and ZnO-based catalysts, pure and mixed in different proportions, supported on γ-Al2O3. Their catalytic performance was studied in the transesterification of soybean oil and castor oil with methanol and butanol, attempting to produce biodiesel. XRD (X-ray diffraction), SEM?EDS (scanning electron microscopy?energy dispersive X-ray spectroscopy), CO2-adsorption and N2-adsorption allowed characterizing the prepared catalysts. The characterization results were in all cases consistent with mesoporous solids with high specific surface area. All the catalysts exhibited good results, especially in the transesterification of castor oil using butanol. For this reaction, the reuse was tested, maintaining high FABE (fatty acid butyl esters) yields after four cycles. This good performance can be attributed to the basic properties of the Mg species, and simultaneously, to the amphoteric properties of ZnO, which allow both triglycerides and free fatty acids to be converted into esters. Using these catalysts, it is possible to obtain second-generation biodiesel, employing castor oil, a raw material that does not compete with the food industry. In addition, butanol can be produced from renewable biomass.